Associations of exposure to individual polyfluoroalkyl substances and their mixtures with vitamin D biomarkers in postmenopausal women - Hong-Xuan Huang; Jun-Xuan Ma; Li-Ying Du; Zi-Hao Xu; Xu-Lian Tang; Cheng-Shen Qiu; Shu-Min Lai; Dan-Qing Liao; Hong-Min Li; Zhi-Yuan Xiong; Bing-Yun Zhang; Ling Kuang; et al. (Ecotoxicology and Environmental Safety)
The potential impact of polyfluoroalkyl substances (PFAS) on vitamin D status in postmenopausal women remains unexplored. This study examined the effects of individual PFAS and their combined exposures on vitamin D biomarkers among 2114 postmenopausal women utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2003–2018. The serum levels of four PFAS compounds, including perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), and perfluorononanoic acid (PFNA), were assessed alongside the 25-hydroxyvitamin D [25(OH)D] level. Our findings indicated that elevated log-transformed PFAS concentrations were significantly associated with reduced 25(OH)D levels (βPFOS: −15.969, 95 % CI: −19.154, −12.785; βPFOA: −17.288, 95 % CI: −22.446, −12.131; βPFNA: −8.510, 95 % CI: −12.148, −4.871; βPFHxS: −4.056, 95 % CI: −7.003, −1.110) and increased odds of vitamin D deficiency (ORPFOS: 2.495, 95 % CI: 1.685, 3.694; ORPFOA: 3.146, 95 % CI: 1.823, 5.429; ORPFNA: 1.906, 95 % CI: 1.357, 2.677; ORPFHxS: 1.480, 95 % CI: 1.109, 1.976). These associations were modified by race, the family incomepoverty ratio and the survey cycle. Notably, non-Hispanic White individuals presented a stronger inverse association between PFOS exposure and 25(OH)D levels. Bayesian kernel machine regression and weighted quantile sum analyses demonstrated that the effects of exposure to mixtures of the four studied PFAS were consistent with the effects of exposure to individual PFAS. These findings indicate that exposure to individual PFAS, particularly PFOA and PFOS, and their four mixtures may adversely affect serum 25(OH)D concentrations in postmenopausal women, underscoring the need for further investigation into the potential impact of PFAS on vitamin D status in this population.